1988
DOI: 10.2307/1940436
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Regulation and Fish Community Structure

Abstract: Many regulated streams are characterized by high variable and unpredictable flow regimes. Since changes in streamflow directly modify physical habitat, streams with such highly variable flows provide highly unstable aquatic habitats. We evaluated the effect of artificial streamflow fluctuations on stream fish communities by comparing fish densities, in species and habitat groups, between two rivers differing in daily flow regime: on with with a natural flow, and one with highly regulated flows. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
351
1
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(372 citation statements)
references
References 49 publications
(55 reference statements)
13
351
1
4
Order By: Relevance
“…1): the first site (in the first transect) was adjacent to one bank, the second (in the second transect) in the centre of the channel and the third (correspondingly in the third channel) adjacent to the opposite bank and so on. At each sampling site fish were captured in an area of approximately 1 m 2 using a pre-positioned electrofishing square (Bain et al, 1985(Bain et al, , 1988Weddle & Lester, 1993). The sampler was a 0.75*0.75 m frame (the effective area of the sampler for the average size of fish captured was approximately 1 m 2 ) electrified through a 10-m extension cord, which was connected to a Honda EG 1900X generator (230-240 VAC, ) positioned on the bank (Fig.…”
Section: Field Samplingmentioning
confidence: 99%
“…1): the first site (in the first transect) was adjacent to one bank, the second (in the second transect) in the centre of the channel and the third (correspondingly in the third channel) adjacent to the opposite bank and so on. At each sampling site fish were captured in an area of approximately 1 m 2 using a pre-positioned electrofishing square (Bain et al, 1985(Bain et al, , 1988Weddle & Lester, 1993). The sampler was a 0.75*0.75 m frame (the effective area of the sampler for the average size of fish captured was approximately 1 m 2 ) electrified through a 10-m extension cord, which was connected to a Honda EG 1900X generator (230-240 VAC, ) positioned on the bank (Fig.…”
Section: Field Samplingmentioning
confidence: 99%
“…La variabilité temporelle des débits est également un facteur pouvant favoriser la diversité (HORWITZ, 1978 ;BAIN et al, 1988), et la durée des périodes pendant lesquelles les conditions d'habitat sont limitantes est à prendre en compte (CAPRA et al, 1995). En particulier, il serait intéressant de mieux quantifier l'intérêt de la modulation temporelle des débits réservés qui existe sur la plupart des RCC (Tableau II), voire de tester I'impact de modulations plus fréquentes qui rendraient les hydrographes des RCC plus proches d'une situation naturelle.…”
Section: Resultsunclassified
“…The West River was another largely wadable stream that was sampled (864 microhabitats) in 1982and 1983(BAIN et al, 1988 producing data on 3,039 fish of 23 species. For brevity, select results are presented for two species representing extrêmes of microhabitat use, and results are summarized for two streams with diverse and well sampled fish faunas.…”
Section: Resultsmentioning
confidence: 99%
“…Thèse were comparative, unregulated and regulated river studies of fish community composition and species-level microhabitat use. Study area descriptions and results of thèse studies have been reported by BAIN et al, 1988 ;KINSOLVING and BAIN, 1993 ;SCHEIDEGGER and BAIN, 1995. Here, I use the data from the unregulated rivers (West River in the northeastern United State [Vermont] and the Cahaba River in the southeastern United States [Alabama]) that were included in the comparative studies.…”
Section: Methodsmentioning
confidence: 99%